2017
DOI: 10.1007/s11010-017-3184-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of spinal cord injuries and potential therapeutic approaches

Abstract: The incidence of spinal cord injuries (SCI) is high every year. As the spinal cord is the highway that allows for the brain to control the rest of the body, spinal cord injuries greatly impact the quality of life of the patients. The SCI include the primary response consisting of the initial accident-induced damage and the secondary response that is characterized by damage due to inflammation and biological responses. Astrocytes are the first to act at the site of the injury, forming a glial scar and attractin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 54 publications
0
44
0
Order By: Relevance
“… 91 , 92 Astrocyte-specific inflammatory signaling plays a key role in the secondary injury after SCI and TBI. 93 , 94 , 95 NFκB signaling has been well known to participate the inflammatory response during the secondary CNS injury. It plays a dual role in the pathogenesis and functional recovery after CNS injury.…”
Section: Innate Immune Response After Cns Injurymentioning
confidence: 99%
“… 91 , 92 Astrocyte-specific inflammatory signaling plays a key role in the secondary injury after SCI and TBI. 93 , 94 , 95 NFκB signaling has been well known to participate the inflammatory response during the secondary CNS injury. It plays a dual role in the pathogenesis and functional recovery after CNS injury.…”
Section: Innate Immune Response After Cns Injurymentioning
confidence: 99%
“…Previous studies have shown that under natural conditions, the local immune microenvironment of SCI is "Yin-Yang" imbalance, and inflammatory cell subsets (such as Th1, Th17, Tc and M1) and factors (such as IL-1b, IL-18, IL-6, IFN-g and TNF-a) are dominant, while anti-inflammatory cell subsets (such as Th2, Treg, Ts, M2, etc.) and factors (such as IL-4, − 10, − 13 and TGF-b) are very rare [5,6,[55][56][57][58][59]. This is an important mechanism of pathological damage following SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary injury refers to local inflammation, edema, ischemia and electrolyte changes, among which inflammation is one of the main damage factors [4,5]. The inflammatory response is characterized by infiltration and activation of inflammatory cells in the injured spinal cords, which leads to the increase of inflammatory cells and inflammatory factors, and formation of inflammatory microenvironment, finally leading to spinal cord dysfunction [6].…”
Section: Introductionmentioning
confidence: 99%
“…Primary injury refers to the direct injury of mechanical force to the spinal cord, which cannot be interfered clinically [3]. Secondary injury refers to local inflammation, edema, ischemia, and electrolyte changes, among which inflammation is one of the main damage factors [4,5]. The inflammatory response is characterized by infiltration and activation of inflammatory cells in the injured spinal cords, which leads to the increase of inflammatory cells and inflammatory factors, and formation of inflammatory microenvironment, finally leading to spinal cord dysfunction [6].…”
Section: Introductionmentioning
confidence: 99%